53.6k views
5 votes
Simplify(√3-√2)(√3+√2): Use this to compute 1/√3-√2 and 1/√3+√2:

User Simplexity
by
8.3k points

1 Answer

1 vote

Answer:

(√3-√2)(√3+√2) = 1

1/√3-√2 = √3+√2

1/√3+√2 = √3-√2

Explanation:

To simplify the expression (√3-√2)(√3+√2), we can use the difference of squares formula, which states that (a-b)(a+b) = a^2 - b^2.

Applying this formula to our expression, we have:

(√3-√2)(√3+√2) = (√3)^2 - (√2)^2

Simplifying further:

= 3 - 2

= 1

So, the simplified expression (√3-√2)(√3+√2) equals 1.

Now, let's compute 1/√3-√2 and 1/√3+√2:

To compute 1/√3-√2, we need to rationalize the denominator. To do this, we multiply both the numerator and the denominator by the conjugate of the denominator, which in this case is √3+√2.

1/√3-√2 = (1/√3-√2) * (√3+√2)/(√3+√2)

Multiplying the numerators and the denominators:

= (√3+√2)/(√3-√2)(√3+√2)

= (√3+√2)/(3-2)

= (√3+√2)/1

= √3+√2

Therefore, 1/√3-√2 simplifies to √3+√2.

Similarly, to compute 1/√3+√2, we multiply both the numerator and the denominator by the conjugate of the denominator, which is √3-√2.

1/√3+√2 = (1/√3+√2) * (√3-√2)/(√3-√2)

Multiplying the numerators and the denominators:

= (√3-√2)/(√3+√2)(√3-√2)

= (√3-√2)/(3-2)

= (√3-√2)/1

= √3-√2

Therefore, 1/√3+√2 simplifies to √3-√2.

In summary:

(√3-√2)(√3+√2) = 1

1/√3-√2 = √3+√2

1/√3+√2 = √3-√2

I hope this explanation helps you understand the simplification and computation process. Let me know if you have any further questions!

User Pigletfly
by
7.7k points